The many faces of diabetes: a critical multimodal analysis of diabetes pages on Facebook - Hunt, Daniel (Elsevier, 2015)
Health communication published on Facebook has become a popular source of medical information and large organisations now utilise Facebook to disseminate multimodal representations of health and illness. Drawing on a sample of posts to two popular diabetes-related Facebook pages, this paper aims to examine the multimodal representation of people with diabetes and consider the implications of this emergent context of health communication. These posts draw upon visual and linguistic features of social intimacy to synthesise personal relationships with their audiences and to foster user involvement with their authoring organisations. The promissory vision of living well with diabetes that predominates on these pages is thus also designed to serve the agendas of organisations who are dependent on user participation to generate revenue.